CEO Compensation, Managerial Overconfidence and Performance of Sharia Compliant Firms and Non-Sharia Compliant Firms: Evidence from Listed GCC Firms - Abdalkrim, Gaafar Mohamed (Archives of Business Research, 2021)
Background: The positive relationship between managerial overconfidence and performance implies that overconfident managers overestimate their ability to create value and improve their firm’s performance, which also lead to overestimate their own firms returns by taking over other firms. Purpose: The study examines relationship between managerial overconfidence, CEO compensation, and performance of sharia compliant firms and non-sharia compliant firms for 207 GCC listed firms from 2010 to 2014. Methodology: The study sample comprised of 207 firms for the main empirical analysis. The data used in this study were collected from GCC stock exchange data-base and firms financial report provided by website argaam.com between 2010 and 2018. Findings: The study found that managerial overconfidence is positively and significantly related to firm performance. CEO compensation and managerial overconfidence is also associated positively with sharia–compliant firms’ performance. The findings supported first hypothesis that managerial overconfidence leads to better firms’ performance. Originality: The study has revealed a positive impact of sharia compliant firms’ managerial overconfidence on firm performance. Furthermore, the effect of CEO compensation is favorable in sharia compliant firms.